Forensic View of Suicide in Healthcare Workers - Deeksha Pandey; Shambhuvi NA; Ahongsangbam Sanathoi Chanu; Adil Hussain; Anshika Rosha; Mamta Bhandari; Vinod Bhatt (Indian Journal of Forensic Medicine and Pathology, 2025)
Background: Suicide among healthcare workers, particularly doctors and nurses, has emerged as a major concern both for forensic experts and public health professionals.1 The emotionally taxing nature of their roles, exposure to trauma, easy access to lethal substances, and high workload contribute to an increased risk of suicide. Aim: To explore the forensic aspects, patterns, and medico-legal implications of suicide among healthcare workers and evaluate the role of forensic investigations in identifying causes and occupational linkages. Objectives: 1. To assess the prevalence and occupational risk factors for suicide in healthcare professionals. 2. To review forensic pathology and autopsy𿿿ndings in these cases. 3. To evaluate medico-legal protocols and recommend preventive strategies. Material: An integrative review of literature from PubMed, Scopus, and other indexed databases covering forensic case reports, autopsy studies, psychological autopsy data, and medico-legal investigations from 2010 to 2024. Result: The analysis indicates that suicide in healthcare professionals is underreported due to stigma and institutional concerns. Common methods include medication overdose (35%), hanging (30%), and self-poisoning (15%). Forensic investigations frequently show usage of hospital medications or familiarity with lethal procedures. Mental health histories often reveal untreated depression, burnout, or anxiety, all exacerbated by occupational pressures.2,6,7 Conclusion: Understanding the forensic and medico-legal dimensions of suicides in healthcare workers is vital for prevention and legal accountability. Forensic pathologists play a key role in establishing occupational causes, ruling out negligence or foul play, and supporting institutional reforms.3,10